Essential Genetics A Genomics Perspective - Hartl, Daniel L (Jones & Bartlett Learning, 2014)
Updated throughout to reflect the latest discoveries in this fast-paced field, this Sixth Edition, provides an accessible, student-friendly introduction to modern genetics. Designed for the shorter, less comprehensive course, the Sixth Edition presents carefully chosen topics that provide a solid foundation to the basic understanding of gene mutation, expression, and regulation. It goes on to discuss the development and progression of genetics as a field of study within a societal and historical context. The Sixth Edition includes new learning objectives within each chapter which helps students identify what they should know as a result of their studying and highlights the skills they should acquire through various practice problems